2018
DOI: 10.1002/ece3.3857
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phylogenetic diversity determine woody productivity in a temperate forest

Abstract: Understanding the relationships between biodiversity and ecosystem productivity has become a central issue in ecology and conservation biology studies, particularly when these relationships are connected with global climate change and species extinction. However, which facets of biodiversity (i.e. taxonomic, functional, and phylogenetic diversity) account most for variations in productivity are still not understood very well. This is especially true with regard to temperate forest ecosystems. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 68 publications
(147 reference statements)
2
58
1
Order By: Relevance
“…While grain-dependent shifts are often expected (Table 1), this had not been shown previously with empirical data for S→NPP using spatial grains coarser than several hectares (Luo et al;Chisholm et al, 2013;Hao et al, 2018). If the S→NPP direction is the real causal one, then our results from SEM and RF analyses support several theoretical expectations (Table 1) and give further impetus to efforts quantifying biodiversity effects in naturally assembled ecosystems at broad spatial scales .…”
Section: Discussionsupporting
confidence: 82%
“…While grain-dependent shifts are often expected (Table 1), this had not been shown previously with empirical data for S→NPP using spatial grains coarser than several hectares (Luo et al;Chisholm et al, 2013;Hao et al, 2018). If the S→NPP direction is the real causal one, then our results from SEM and RF analyses support several theoretical expectations (Table 1) and give further impetus to efforts quantifying biodiversity effects in naturally assembled ecosystems at broad spatial scales .…”
Section: Discussionsupporting
confidence: 82%
“…species richness, Shannon diversity, functional diversity and phylogenetic diversity) of the same functional group were simultaneously analysed as predictors of a certain ecosystem function (e.g. Hao et al, ), I regarded these collectively as a single BEF relationship. Based on these criteria, I found 726 published BEF relationships in naturally assembled communities.…”
Section: Quantitative Response Of Ecosystem Functioning To Biodiversimentioning
confidence: 99%
“…Nevertheless, cases in which effects of functional diversity were strongest ( N = 12, e.g. Paquette & Messier, ; Hao et al, ) strongly outnumbered cases where phylogenetic diversity was more important ( N = 3, e.g. Hao et al, ) (χ 2 = 5.40; P = 0.0201).…”
Section: Relative Importance Of Biodiversitymentioning
confidence: 99%
“…Given the complexity of factors that determine species diversity along environmental changes the use of structural equation model (SEM) is a powerful tool to test direct and indirect causal effects with a series of dependent and independent variables that may be correlated (Grace et al 2010, Lamb et al 2014, Hao et al 2018. For example, a study using SEM revealed that species diversity of mammals depends directly on environmental factors while functional diversity depends on the species evolutionary history (Oliveira et al 2016).…”
Section: Introductionmentioning
confidence: 99%